Phenotypic findings associated with variation in elastin - Anne Justice; Melissa A. Kelly; Gary Bellus; Joshua D. Green; Raza Zaidi; Taylor Kerrins; Navya Josyula; Teresa R. Luperchio; Beth A. Kozel; Marc S. Williams (HGG Advances)
Summary: Variation in the elastin gene (ELN) may contribute to connective tissue disease beyond the known disease associations of supravalvar aortic stenosis and cutis laxa. Exome data from MyCode Community Health Initiative participants were analyzed for ELN rare variants (mean allele frequency <1%, not currently annotated as benign). Participants with variants of interest underwent phenotyping by dual chart review using a standardized abstraction tool. Additionally, all rare variants that met inclusion criteria were collapsed into an ELN gene burden score to perform a phenome-wide association study (PheWAS). Two hundred and ninety-six eligible participants with relevant ELN variants were identified from 184,293 MyCode participants. One hundred and three of 254 living participants (41%) met phenotypic criteria, most commonly aortic hypoplasia, arterial dilation, aneurysm, and dissection, and connective tissue abnormalities. ELN variation was significantly (p < 2.8 × 10−5) associated with “arterial dissection” in the PheWAS and two connective tissue Phecodes approached significance. Variation in ELN is associated with connective tissue pathology beyond classic phenotypes.